Empathy and Theory of Mind: One Underlying Cognitive Mechanism - Truzzi, Anna (2016)
Theory of Mind (ToM) is defined as the ability to attribute mental states to others and to recognize that other minds have beliefs, desires, and intentions which are different from one’s own mind. ToM is a multilevel phenomenon that progresses from early beginnings to more complex elaborations, mediated by higher order cognition and develops with socialization. Traditionally thought to be a concept within the domain of cognitive psychology, we argue that ToM ability may be better defined as empathy. We propose a model to study how attributing mental states to others and oneself should be assessed from multiple levels, beginning with physiological determinants to interacting with the psychological, social, and cultural environment.